Malaysia and the Rome Statute of the International Criminal Court - Hassan, Fareed Mohd; Mohd Rusli, Mohd Hazmi Bin; Tajudin, Amalina Ahmad (Brawijaya Law Journal, 2022)
Through its founding treaty, the Rome Statute, the establishment of the International Criminal Court (ICC) has received support and opposition from many countries. Despite working toward universal ratification or accession to the Rome Statute, Signatories and State Parties to the Rome Statute have decided not to ratify and withdraw from being Member States due to, among other reasons, the issue of immunity and criminal responsibility of the Head of State, which are not in line with their respective Constitution, particularly by Malaysia. As such, this study analyzes the position of immunity of the Head of State as well as the criminal responsibility of a military commander under international law, particularly under the Rome Statute and the Malaysian Constitution. Based on doctrinal analysis, this study argues that the Yang di-Pertuan Agong, as the Malaysian Head of State and the Commander-in-Chief of the Malaysian Armed Forces, has immunity before the national court and, thus, will be highly exposed to ICC jurisdiction because the complementary principle under the Rome Statute cannot be implemented. This study concludes that being a part of the ICC Membership is untimely for Malaysia without the reconciliation of these contradictions.